Povezanost rezultatov doseženih v izbranih telesnih merah in testih gibalnih sposobnosti z oceno tekmovalne uspešnosti pri rokometaših - Šibila, Marko (Šport (Ljubljana), 2019)
The contribution presents the relationship between the assessment of handball players% playing performance and their results in terms of sprint velocity, take-off power, sprinting endurance and VO2max. The study involved 239 male handball players, aged between 15 and 31 (20.13 +- 3.03 years). Their average body height was 187.54 +- 6.29 cm and body mass 88.36 +- 10.51 kg. They were divided into seven groups according to their playing position: 11 Slovenian handball coaches with international experience assigned each individual into one of five quality classes. Based on the results obtained, we can conclude that the indicators of sprint quality, take-off power, sprinting endurance, VO2max, speed of set shot and jump shot as well as body height and body mass are statistically significantly positively correlated with the assessment of playing performance - this applies to the entire group and to individual playing positions as well. Among all the variables, the highest and statistically significantly positive correlation with playing performance was observed in both shots, a half-squat jump and a countermovement jump. The quantity of subcutaneous fat and the endomorphic component of the somatotype were statistically significantly most negatively correlated with the assessment of playing performance.
Keywords: anthropometry; antropometrija; competitive performance; gibalne sposobnosti; handball; motor abilities; motorika; rokomet; sport; šport; tekmovalna uspešnost; telesne mere